Foot, hand and mouth disease. Case presentation - Deyanira Cabrera Escobar; Anet Ramos Plasencia; Leticia Espinosa González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foot, hand and mouth disease is a highly contagious disease, caused by the A16 Coxsackie virus and 71 enterovirus. The transmission occurs by the direct contact with nasal and oral secretions or fecal material and sprayed drops, in an oral fecal or fecal oral route and through contaminated objects. A case of a 4 year old patient came to the dental office due to the presence of painful blisters in the oral mucosa which made his feeding difficult. In addition he had a rash in hands and feet. After prescribing dental treatment he was referred to the pediatrician of his health area who conclude the diagnosis of foot, hand and mouth disease. The oral component is generally the main symptom and the chief complaint, however, its almost unknown in its oral profile. That is the reason for the interest of this presentation because knowing its physiopathology and the clinical characteristics of the presentation allows differential diagnosis and clinically suspect the disease.